Revisiting community policing in Ukraine: lessons for police reform - Chistyakova, Yulia (2010)
This thesis critically revisits a project in community policing transfer to Ukraine. It examines the genesis, context and impact of the project and 'through this lens explores how community policing can be problematic in a former Soviet society. The study is intended to contribute to debates on the issues of reforming post-Soviet policing and the potential role of criminological imports in this process. The thesis highlights the obstacles to, and challenges of developing community policing within the context of the continued dominance and expanding scope of informal shadowy practices in the governance of policing. It demonstrates the importance of a combination of historical, economic, social and political factors impacting upon the willingness of people in Ukraine to contact the police and engage in crime prevention, and explores why people in Ukraine do not see themselves part of a 'community'. Normative questions posed by the notion of 'public engagement' are also explored. It is argued that 'community policing' as a consensual coproduction of order and safety is unlikely in Ukraine. Community policing practice in this context has a potential to evolve as an authoritarian, moralistic, coercive and exclusive form of control. The thesis challenges the assumption that export of community policing is an unproblematic transfer of expertise and 'best practice', and highlights the problematic nature of the relations between funders, academic entrepreneurs, the local police, academics and the non-governmental sector. The thesis also demonstrates how a commitment to scientific rationalism and a narrow conceptualisation of 'evidence' in evaluation research has political implications